2004
DOI: 10.1096/fj.03-0886fje
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐derived growth factor stimulates LAT1 gene expression in vascular smooth muscle: Role in cell growth

Abstract: Platelet-derived growth factor (PDGF) contributes to vascular disease by stimulating the growth of vascular smooth muscle cells (SMCs). Since amino acids are required for cell growth, the present study examined the effect of PDGF on system L amino acid transport, which is the predominant cellular pathway for the uptake of essential amino acids. System L amino acid transport was monitored by measuring the uptake of L-leucine. Treatment of SMCs with PDGF stimulated L-leucine transport in a concentration- and tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 27 publications
(30 reference statements)
2
55
0
Order By: Relevance
“…A hallmark of these two systems is that they are subject to extensive adaptive, hormonal, and osmotic regulation (Collarini and Oxender, 1987;Palacín et al, 1998). A nutrition signaling cascade that includes activation of phosphatidylinositol 3-kinase (PI3K) and mammalian target of rapamycin (mTOR) has been shown to be important for induction of system A and system L activities (Peyrollier et al, 2000;Liu et al, 2004). In hepatocytes, insulin regulates expression of SN1 through the PI3K-mTor signaling cascade (Gu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A hallmark of these two systems is that they are subject to extensive adaptive, hormonal, and osmotic regulation (Collarini and Oxender, 1987;Palacín et al, 1998). A nutrition signaling cascade that includes activation of phosphatidylinositol 3-kinase (PI3K) and mammalian target of rapamycin (mTOR) has been shown to be important for induction of system A and system L activities (Peyrollier et al, 2000;Liu et al, 2004). In hepatocytes, insulin regulates expression of SN1 through the PI3K-mTor signaling cascade (Gu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that LAT1 is overexpressed in some tumor tissues [34,35] and is actively involved in the proliferation of vascular smooth muscle cells [36]. In order to investigate whether or not LAT1 is involved in the proliferation of breast cancer cells, we employed BCH, a selective inhibitor of LAT1 [37,38], to inhibit the proliferation of malignant MDA-MB-231 cells.…”
Section: Blockade and Downregulation Of Lat1 Inhibits The Proliferatimentioning
confidence: 99%
“…[1][2][3] In this model, signals arising from the extracellular milieu as growth factors 4,5 and nutrient availability, 6,7 from changes of transporter activity at the cell membrane 8,9 or directly from intracellular metabolic changes affecting internal amino-acid levels [9][10][11][12][13] and ATP availability [14][15][16] all feed into mTOR which, by integrating this information, couples the cellular metabolic state to downstream targets that modulates rates of translation and thereby cell mass and number. 17 mTOR, also known as FKBP12-rapamycin-associated protein (FRAP) 18 /rapamycin and FKBP12 target (RAFT-1) 19 with its putative raptor, 20,21 G protein b-subunit-like protein (GbL) 22 and tuberous sclerosis complex (Tsc)/Ras-related protein (Rheb) 3,12 regulators, modulate the phosphorylation state of p70 ribosomal S6 kinase 1 (S6K1) and other downstream effectors.…”
Section: Introductionmentioning
confidence: 99%